2001
DOI: 10.1046/j.1471-4159.2001.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Similarities and differences in the neuronal death processes activated by 3OH‐kynurenine and quinolinic acid

Abstract: 3OH-Kynurenine and quinolinic acid are tryptophan metabolites able to cause, at relatively elevated concentrations, neuronal death in vitro and in vivo. In primary cultures of mixed cortical cells, the minimal concentration of these compounds leading to a signi®cant degree of neurotoxicity decreased from 100 to 1 mM, when the exposure time was prolonged from 24 to 72 h. NMDA receptor antagonists and inhibitors of nitric oxide synthase or poly(ADP-ribose) polymerase reduced quinolinic acid, but not 3OH-kynureni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 50 publications
2
69
2
Order By: Relevance
“…29 Therefore, the findings indicate that pharmacological normalization of stress-induced KYN pathway hyperactivity by IDO1 inhibition normalizes memory processing of aversive stimuli, and to a similar extent but via a different mechanism to that of escitalopram. With regard to mechanism-of-action on memory processes, both 3-HK and QUIN can induce oxidative stress and excitotoxicity in neurons, particularly when elevated chronically (Chiarugi et al, 2001;Haroon et al, 2012;Schwarcz et al, 2012). A limitation of the current study, given their important effects at several neurotransmitter-receptor types, was that QUIN and KYNA could not be measured in small brain-tissue samples.…”
Section: Ido1 Inhibition Blocks Kynurenine Pathway Activation and Excmentioning
confidence: 88%
See 1 more Smart Citation
“…29 Therefore, the findings indicate that pharmacological normalization of stress-induced KYN pathway hyperactivity by IDO1 inhibition normalizes memory processing of aversive stimuli, and to a similar extent but via a different mechanism to that of escitalopram. With regard to mechanism-of-action on memory processes, both 3-HK and QUIN can induce oxidative stress and excitotoxicity in neurons, particularly when elevated chronically (Chiarugi et al, 2001;Haroon et al, 2012;Schwarcz et al, 2012). A limitation of the current study, given their important effects at several neurotransmitter-receptor types, was that QUIN and KYNA could not be measured in small brain-tissue samples.…”
Section: Ido1 Inhibition Blocks Kynurenine Pathway Activation and Excmentioning
confidence: 88%
“…One candidate stress-activated inflammation pathway, including for induction of hyperfearfulness, is the kynurenine pathway: increased TNF-, IL-6 and interferon- (IFN-) increase expression of indoleamine 2,3-dioxygenase (IDO1) and tryptophan 2,3-dioxygenase (TDO2), enzymes expressed by immune cells and other cell types in various tissues, that promote tryptophan (TRP) catabolism to kynurenine (KYN) in periphery and brain (Dai and Zhu, 2010;Gibney et al, 2014;Robinson et al, 2003;Vecsei et al, 2013;Werner-Felmayer et 6 al., 1989). KYN is further metabolized to, among others, 3-hydroxykynurenine (3-HK), quinolinic acid (QUIN) and kynurenic acid (KYNA), catabolites that can contribute to oxidative stress, excitotoxicity, and neuroprotection (for review: (Chiarugi et al, 2001;Haroon et al, 2012;Schwarcz et al, 2012). There is growing evidence for kynureninepathway hyperfunction in stress-related disorders, particularly for MDD (Bay-Richter et al, 2015;Kim et al, 2012;Reus et al, 2015;Savitz et al, 2015;Steiner et al, 2011;Sublette et al, 2011) (for review: (Maes et al, 2011)).…”
Section: Introductionmentioning
confidence: 99%
“…Sequential activation by the enzymes kynurenine monooxygenase (KMO) and kynureninase results in the formation of the neurotoxic molecules 3-hydroxy kynurenine (3HK), anthranilic acid (AA), 3-hydroxy anthranilic acid (HANA), and QUIN that are ultimately converted to nicotinic acid adenine dinucleotide (NAD). 3HK, AA and, HANA all are known to trigger profound oxidative stress and precipitate cell death (Chiarugi et al, 2001a;Chiarugi et al, 2001b;Guidetti and Schwarcz, 1999). They also indirectly contribute to glutamate increases by increasing the need for GSH and activating the xC-system.…”
Section: Kyn Pathway and Its Downstream Metabolitesmentioning
confidence: 99%
“…QUIN is an endogen Nmethyl-D-aspartate (NMDA) receptor agonist [55]. At micromolar concentrations, the excitotoxic effect of QUIN can be mimicked in primary cortical neuronal cell cultures [56]. The same effect is found in vivo where intracerebral injection of QUIN induces excitotoxic lesions [17].…”
Section: Possible Mechanisms Of Ido-mediated Tolerance Inductionmentioning
confidence: 99%
“…Interestingly, the clinical disease severity and the QUIN concentration in the cervicolumbar spinal cord correlate well [81]. Immunohistochemical studies have shown that enzymes of the kynurenine pathway such as the IDO and kynurenine 3-mono-xygenase are mainly expressed by infiltrating macrophages/activated microglia in the perivascular/juxtavascular area during the acute phase of EAE [15,56]. IDO expression and activity is increased in the acute and remission phase of EAE.…”
Section: The Kynurenine Pathway In Eae and Msmentioning
confidence: 99%